2023
DOI: 10.3390/biomimetics8060500
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Design Rules from Highly Mineralized Natural Composites for Two-Dimensional Composite Design

Anamika Prasad,
Vikas Varshney,
Dhriti Nepal
et al.

Abstract: Discoveries of two-dimensional (2D) materials, exemplified by the recent entry of MXene, have ushered in a new era of multifunctional materials for applications from electronics to biomedical sensors due to their superior combination of mechanical, chemical, and electrical properties. MXene, for example, can be designed for specialized applications using a plethora of element combinations and surface termination layers, making them attractive for highly optimized multifunctional composites. Although multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 226 publications
0
1
0
Order By: Relevance
“…To mitigate the need for computationally demanding numerical modeling, various sophisticated numerical modeling strategies have been introduced. These include approaches such as nonlinear homogenization [17] and multiscale methods [18,19]. In recent works, it has been demonstrated that bioinspired nacre-like composite materials may be optimized to improve their mechanical performance under static loadings [20,21],…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the need for computationally demanding numerical modeling, various sophisticated numerical modeling strategies have been introduced. These include approaches such as nonlinear homogenization [17] and multiscale methods [18,19]. In recent works, it has been demonstrated that bioinspired nacre-like composite materials may be optimized to improve their mechanical performance under static loadings [20,21],…”
Section: Introductionmentioning
confidence: 99%